2010
DOI: 10.1637/8773-033109-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Vaccination in Chickens and Pigs with Replication-Competent Adenovirus–Free Human Recombinant Adenovirus 5

Abstract: SUMMARY Protective immunity to avian influenza (AI) virus can be elicited in chickens by in ovo or intramuscular vaccination with replication-competent adenovirus (RCA)-free human recombinant adenovirus serotype 5 (Ad5) encoding AI virus H5 (AdTW68.H5) or H7 (AdCN94.H7) hemagglutinins. We evaluated bivalent in ovo vaccination with AdTW68.H5 and AdCN94.H7 and determined that vaccinated chickens developed robust hemagglutination inhibition (HI) antibody levels to both H5 and H7 AI strains. Additionally, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…HPAI of the H5 and H7 subtypes remain a constant concern in the world poultry industry. This has led the World Organization for Animal Health and the Food and Agricultural Organization of the United Nations to recommend vaccination of poultry . Several viral vectors expressing HA constructs have been shown to be immunogenic and protective against HPAI challenge .…”
Section: Resultsmentioning
confidence: 99%
“…HPAI of the H5 and H7 subtypes remain a constant concern in the world poultry industry. This has led the World Organization for Animal Health and the Food and Agricultural Organization of the United Nations to recommend vaccination of poultry . Several viral vectors expressing HA constructs have been shown to be immunogenic and protective against HPAI challenge .…”
Section: Resultsmentioning
confidence: 99%
“…Another study of live IB vaccination in 1-day-old chickens also showed an inefficient antibody response and the protective efficacy of the vaccine mostly correlated with induction of high levels of CD4+, CD8+ and IgA bearing B cells [ 64 ]. Also, the vaccination of 1 day old chickens with adenovirus vectored H5 and H7 influenza vaccine could induce IgA response in lachrymal fluid and increased interleukin-6 expression without inducing detectable levels of serum antibodies [ 65 ]. Therefore, our current findings are consistent with previous reports in that LAIV enhances mucosal IgA response and provides viral clearance that is less dependent on serum antibody response in young chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of the bivalent vaccine by a mass vaccination route by course spray to 1-day-old chickens induced local IgA antibodies in tears but no detectable serum antibodies [231]. Importantly, the induction of anti-H7 antibodies was not impaired even in the presence of anti-Ad5 antibodies [229,231].…”
Section: Adenovirus (Ad-5)mentioning
confidence: 93%
“…In ovo vaccination with monovalent adenovirus-H7 or bivalent adenovirus H7-H5 HA recombinant vaccines induced high antibody titres between 25 and 45 days after hatch [229,231]. Administration of the bivalent vaccine by a mass vaccination route by course spray to 1-day-old chickens induced local IgA antibodies in tears but no detectable serum antibodies [231]. Importantly, the induction of anti-H7 antibodies was not impaired even in the presence of anti-Ad5 antibodies [229,231].…”
Section: Adenovirus (Ad-5)mentioning
confidence: 97%
See 1 more Smart Citation